Perceptions of HRM system strength and affective commitment: the role of human relations and internal process climate. Issue 21 (30th November 2019) - Cafferkey, Kenneth; Heffernan, Margaret; Harney, Brian; Dundon, Tony; Townsend, Keith
Abstract: Traditional HRM research has predominantly focused on both the content and/or bundling of HR practices, typically reported by managerial respondents. This paper extends knowledge by examining the diffusion of HR processes as an indication of HRM system strength using employee data. Specifically, we examine the impact of the distinctiveness, consistency and consensus generated by the HRM system and its impact on employee affective commitment and the potential mediating role of human relations climate and moderating role of internal process climate in this relationship. The results from a sample of 585 employees across a diverse range of organisations in Malaysia lend support to the key hypotheses. These findings are significant in supporting the value of a process perspective and the application of HR practices. They also offer important insights from the under-researched and non-western context of Malaysia.